Pengaruh Model Pembelajaran Berbasis Masalah Berbantuan Mobile Pocket Book Fisika Terhadap Kemampuan Pemecahan Masalah Peserta Didik - Rindayu Noviatika; Gunawan Gunawan; Joni Rokhmat (Department of Physics Education, Universitas Mataram, 2019)
This study aims to determine the effect of problem-based learning models assisted by pocket book physics on problem-solving abilities. The type of research used was quasi-experimental design with pretest-posttest control group design. The population in this study were all students of class X MIPA Senior High School in Mataram. The research sample was taken using cluster random sampling technique, so that the selected students of class X MIPA five were 31 people as the experimental class and the X class MIPA six as many as 27 people as the control class. The experimental class was treated in the form of a problem-based learning model assisted by pocket book physics mobile and the control class was treated in the form of conventional learning. The instrument used to measure problem solving ability is a test instrument in the form of a descriptive test of five items. The research hypothesis was tested using the t-test with a significance level of 5%. The t-test produces a t-count value of problem solving ability of 5.832 which is smaller than ÃÂ which is equal to 2.003 so that H0 is rejected and Ha is accepted. So it can be concluded that there is the influence of the problem-based learning model assisted by pocket book physics on students' problem solving abilities. This result can be proven by the N-gain test, where there is an increase in problem solving abilities of 60% for the experimental class and the control class by 34% with the medium category.